Young children with special needs : an introduction to early childhood special education - Gargiulo, Richard M.; Kilgo, Jennifer L. (Albany, NY : Delmar/Thomson Learning, 2000)
Perspectives, policies, and practices of early childhood special education. Identifuing and assessing young children with special needs. Planning and organizing educational programs. A look to the future.
Keywords: Education; Handicapped children; Special education; Handicapped children -- Education (Early childhood)